Analysis of control methods for buck DC-DC converter - Norsyafiera, Nawang (2012)
A DC to DC converter is an electronic circuit which converts a source of direct current (DC) from one voltage level to another. There are three main topologies of converters which are buck converter, boost converter and buck-boost converter. This project is focus on Buck dc-dc converter using the hysteresis, PID and three-level hysteresis controllers. The buck dc-dc converter used to step down the input dc voltage from 24V to 12V. The hysteresis, PID and three-level hysteresis controllers are applied to control the switching of the switching device in buck converter so that the output voltage can be maintained 12V. The PID controller is the most common used in feedback control. The good output voltage can be obtained by well-tuning the P, I and D gains. The hysteresis control is a simplest method and inexpensive and easy in designing. The hysteresis band is derived from the converter current to predict the output voltage after the switching action. The term PID is defined as P for proportional, I for integral and D for derivative. The complete converter circuit is designed and implemented in MATLAB Simulink software. The analyses are carried out by make a comparison of the output voltage and load changes for all controllers.